Application of Grey Numbers to Assessment of Mathematical Modeling Capacities - Michael Gr. Voskoglou (International Journal of Trends in Mathematics Education Research, 2018)
Mathematical modeling appears today as a dynamic tool for teaching and learning mathematics, because it connects mathematics with real world applications thus increasing the student interest on the subject. In the present paper a method is developed that uses grey numbers for evaluating student mathematical modeling capacities and a classroom application is presented illustrating it. This new assessment method is useful in particular when the student performance is evaluated with linguistic characterizations (grades) and not with numerical scores, which makes non feasible the calculation of the mean value of those grades. Grey numbers are indeterminate numbers which are defined with the help of the real intervals and they have found nowadays many applications in real life, science and engineering for handling approximate data.